2017
DOI: 10.1093/nar/gkw1343
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insights into type I toxin antitoxin systems inHelicobacter pylori:the importance of mRNA folding in controlling toxin expression

Abstract: Type I toxin-antitoxin (TA) systems have been identified in a wide range of bacterial genomes. Here, we report the characterization of a new type I TA system present on the chromosome of the major human gastric pathogen, Helicobacter pylori. We show that the aapA1 gene encodes a 30 amino acid peptide whose artificial expression in H. pylori induces cell death. The synthesis of this toxin is prevented by the transcription of an antitoxin RNA, named IsoA1, expressed on the opposite strand of the toxin gene. We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(97 citation statements)
references
References 47 publications
5
88
0
Order By: Relevance
“…A new type I TA system, the AapA1/IsoA1 locus, present on the chromosome of H. pylori, was recently characterized (374). Several type II TA systems associated with the bacterial persistence phenotype have also been localized in this pathogen, including (i) the HP0894-HP0895 proteins (375,376), (ii) the HP0892-HP0893 proteins (RelE-family TA system), and (iii) the HP0967-HP0968 proteins (Vap family) (374).…”
Section: Toxin-antitoxin Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…A new type I TA system, the AapA1/IsoA1 locus, present on the chromosome of H. pylori, was recently characterized (374). Several type II TA systems associated with the bacterial persistence phenotype have also been localized in this pathogen, including (i) the HP0894-HP0895 proteins (375,376), (ii) the HP0892-HP0893 proteins (RelE-family TA system), and (iii) the HP0967-HP0968 proteins (Vap family) (374).…”
Section: Toxin-antitoxin Systemsmentioning
confidence: 99%
“…These systems were encoded by the pVir plasmid, which is involved in virulence and natural transformation. VirT belongs to the RelE family, one of the best-studied TA systems (374,377).…”
Section: Toxin-antitoxin Systemsmentioning
confidence: 99%
“…A global RNA transcript mapping study revealed a number of putative type I toxin‐antitoxin (TA) systems . New work demonstrated rapid killing by the small peptide toxin of these systems, possibly by depleting ribosomal RNAs, and established a fascinating mechanism of post‐translational regulation . The aapA1 toxin full‐length transcript is not competent for translation due to long‐range base pairing interactions between the 3′ and 5′ ends.…”
Section: Regulation Of Virulencementioning
confidence: 99%
“…42 New work demonstrated rapid killing by the small peptide toxin of these systems, possibly by depleting ribosomal RNAs, and established a fascinating mechanism of post-translational regulation. 43 The aapA1 toxin full-length transcript is not competent for translation due to long-range base pairing interactions between the 3′ and 5′ ends. This transcript is processed by an unknown nuclease leading to an altered secondary structure that is translation competent.…”
Section: Post-transcriptional Regulationmentioning
confidence: 99%
“…Four families (A-B-C-D) of conserved type I TA systems are expressed from the chromosome of H. pylori, only the A family was studied as it is highly expressed and conserved among H. pylori strains (23)(24)(25). For the A1 TA system, the detailed mechanism by which transcription of the IsoA1 antitoxin RNA impairs AapA1 toxin synthesis by base pairing with its primary transcript, ensuring both translation inhibition of the AapA1 active message and leading to rapid degradation of the duplex by RNase III, has been recently published (24,25). The H. pylori type I toxins are typically small hydrophobic peptides of 30-40 amino acids predicted to form alpha-helices (26).…”
Section: Introductionmentioning
confidence: 99%